Konsep Desain Sistem Informasi Manajemen Berkas Terpusat di Lembaga Amil Zakat Menggunakan Perspektif Nirlaba - Hanifah Permatasari; Indah Nofikasari (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
The Amil Zakat Institution (LAZ) is a private non-profit organization that assists the Government of Indonesia in managing zakat. LAZ will produce performance reports and financial reports every year to ensure the accountability of the institution. The report is crucial, because it is the result of the performance of all LAZ partners and branch offices, so it must be stored and controlled properly. This performance reporting will be done centrally, so that in the process of making it, some authentic evidence that can be used as proof that it has been accepted and happened, or as a reference and complement, must be managed and distributed efficiently. The file management information system is a solution that can be applied for the management of report materials and the storage of valid reports. This research has resulted in business process flow design, system activity design, and file management information system interface design on LAZ. The theory of accountability of non-profit organizations is used as an analytical study along with the PIECES parameters, to ensure that the resulting design is in accordance with the supposed accountability. The design in this study has been presented systematically, so that it can be understood by LAZ managers or executives who are not from the information technology field.